Desarrollo de portafolios para el aprendizaje y la evaluación : procesos y principios - Klenowski, Val, 1952- (Educación hoy (Narcea (Firm)). Estudios ;, 2014)
Drawing on the author's own experience of using and researching student portfolios, this book analyses the implications for the development of the portfolio for assessment. The portfolio is a file of course work gathered throughout schooling.